What is a short story? - Guillain, Charlotte (Chicago, Illinois Heinemann Raintree, 2015)
Using great examples from past and present, this book explains clearly what is meant by a short story, then prompts children to write their own!
A gift from book Africa
Arts
1 2 13 15
Keywords: Short story -- Authorship -- Juvenile literature; Short story